The Influence of Service Quality and Location on Repurchase Intention at Natra Bintan, A Tribute Portfolio Resort - Rabby Dwi Yendri; Hermansyah (Pt. Threeple Herphi Educate, 2025)
This study investigates the influence of service quality and location on repurchase intention among guests at Natra Bintan, a Tribute Portfolio Resort, in the Riau Islands, Indonesia—a region experiencing rapid tourism growth and intensifying hospitality competition. Employing a quantitative research design with a causal-associative approach, data were collected through a purposive sampling technique from 175 respondents using a structured, closed-ended questionnaire measured on a five-point Likert scale. Validity and reliability tests confirmed that all measurement items were valid and internally consistent, while classical assumption tests verified that the regression model met normality, heteroscedasticity, and multicollinearity requirements. Multiple linear regression analysis revealed that service quality (β = 0.450, p < 0.001) and location (β = 0.108, p = 0.002) both have positive and statistically significant effects on repurchase intention, with service quality identified as the stronger predictor. Simultaneously, both variables explain 32.7% of the variance in repurchase intention, indicating the importance of enhancing service excellence and leveraging strategic location to sustain guest loyalty. The findings contribute to hospitality literature by reinforcing the dual role of service performance and locational attributes in shaping behavioral intentions and offer practical implications for resort managers to integrate operational service improvement with destination accessibility strategies to maintain competitive advantage.